Replacement of animal fat with fractionated and partially hydrogenated palm oil in beef burgers - A. S. Babji; A. R. Alina; M. Y. Seri Chempaka; T. Sharmini; R. Basker; S. L. Yap (Taylor & Francis, 2024)
Indexed by SCOPUS